ANALYSIS OF THE REPAIR METHODS FOR EDGE STRIP OF FRONT SPAR OF CENTRAL WING - XI JiangJing; DONG DengKe; CHEN Li; CHANG Wenui (Jixie qiangdu, 2018)
Aiming at typical connection structure of the bolt holes errors on edge strip of front spar of central wing,this paper analyzes the fatigue property of the structure. The fatigue life of the structure is analyzed by means of structure durability analysis theory. The detail fatigue rating is worked out by finite element analysis and through experimental verification; this paper studies the changes of fatigue life and detail fatigue rating between structure with manufacturing errors and the original structure.Through theoretical and experimental analysis,this paper judges the validity of repair methods for the fastening holes error in the current aviation industry and provides theoretical and experiment data support for repairing methods.